Endovascular Rescue Therapies for Refractory Vasospasm After Subarachnoid Hemorrhage: A Prospective Evaluation Study Using Multimodal, Continuous Event Neuromonitoring. Issue 6 (13th February 2017) - Albanna, Walid; Weiss, Miriam; Müller, Marguerite; Brockmann, Marc Alexander; Rieg, Annette; Conzen, Catharina; Clusmann, Hans; Höllig, Anke; Schubert, Gerrit Alexander
Abstract: BACKGROUND: Critical hypoperfusion and metabolic derangement are frequently encountered with refractory vasospasm. Endovascular rescue therapies (ERT) have proven beneficial in selected cases. However, angioplasty (AP) and intraarterial lysis (IAL) are measures of last resort and prospective, quantitative results regarding the efficacy (cerebral oxygenation, metabolism) are largely lacking. OBJECTIVE: To evaluate the efficacy of ERTs for medically refractory vasospasm using multimodal, continuous event neuromonitoring. METHODS: To detect cerebral compromise in a timely fashion, sedated patients with aneurysmal subarachnoid hemorrhage received continuous neuromonitoring (pti O2 measurement, intraparenchymal microdialysis). ERT (AP and/or IAL) was considered in cases of clinically relevant vasospasm refractory to conservative treatment measures. Oxygen saturation and cerebral and systemic metabolism before and after events of ERT was recorded. RESULTS: We prospectively included 13 consecutive patients and recorded a total of 25 ERT events: AP (n = 10), IAL (n = 11), or both (AP + IAL, n = 4). Average cerebral pti O2 was 10 ± 11 torr before and 49 ± 22 torr after ERT ( P < .001), with a lactate-pyruvate ratio decreasing from 146.6 ± 119.0 to 27.9 ± 10.7 after ERT ( P < .001). Comparable improvement was observed for each type of intervention (AP, IAL, or both). No significant alterations in systemic metabolism could be detected after ERT CONCLUSION: Multimodal event neuromonitoring is able to quantify treatment efficacy in subarachnoid hemorrhage-related vasospasm. In our small cohort of highly selected cases, ERT was associated with improvement in cerebral oxygenation and metabolism with reasonable outcome. Event neuromonitoring may facilitate individual and timely optimization of treatment modality according to the individual clinical course.